If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.50x + 0.70(70) = 0.25(114) Multiply 0.70 * 70 0.50x + 49 = 0.25(114) Reorder the terms: 49 + 0.50x = 0.25(114) Multiply 0.25 * 114 49 + 0.50x = 28.5 Solving 49 + 0.50x = 28.5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-49' to each side of the equation. 49 + -49 + 0.50x = 28.5 + -49 Combine like terms: 49 + -49 = 0 0 + 0.50x = 28.5 + -49 0.50x = 28.5 + -49 Combine like terms: 28.5 + -49 = -20.5 0.50x = -20.5 Divide each side by '0.50'. x = -41 Simplifying x = -41
| 3c+2d=-14 | | 5+9r=50 | | 7e^5x+8=.23 | | 2log^7(1-2x)=12 | | 17j+-30=-404 | | 2x-1=7x-2 | | c-5=-16 | | 15x-25y/9x-15y | | 0=r^2+14.2r-760.5 | | 0=r^2+5r-113.1 | | 0=r^2+6r-50.25 | | x+8=-2x-7 | | 1-2(x-4)+7=-4 | | 0=r^2+10r-301.6 | | 12u-241=227 | | x^2+16x-16=0 | | r=a^2b^2 | | 3/4e^3x-8=6 | | r=a^2+2(ab)+b^2 | | 1+(1/2)*3+(6/b*a) | | -26-4x=14-18x | | =1+(1*2) | | x^2-15x+36x=0 | | 3+5=23+x | | K-36/8=6 | | 4x(2+5)2-52= | | n+-3=-7 | | 56=-4+10x | | 9+5x=2x+27 | | 2x^2+3ax=0 | | 54+15g=-90+39g | | 2+11+8r=29 |